Participación de la comunidad y sus organizaciones en la sostenibilidad de proyectos de inversión pública Municipalidad de Chota, 2014 - Cabrera Campos, Eduar Marino (2019)
ABSTRACT The objective of this research is the study of the participation of the community and its organizations in the sustainability of public investment projects of the Municipality of Chota. Faced with the problem described, we formulate our research problem in the following terms: How does the participation of the community and its organizations contribute to the sustainability of public investment projects of the Municipality of Chota? The Population under study was made up of officials and professionals from the management of economic development, planning, management of studies of the Provincial Municipality of Chota and leading actors of the community organizations benefited from the projects and / or public investment activities. Making a total of 100 people, of which a sample was taken for the convenience of 25 people. The result of the research shows that the active participation and organization of the community in the scope of the Municipality of Chota is essential to achieve the sustainability of public investment projects.